Predictors of burden in Australian mental health caregivers: a cross-sectional survey. (4th July 2021) - Stomski, N. J.; Morrison, P.
Abstract: Background: The shift towards providing mental healthcare in the community has resulted in caregivers becoming more involved in the delivery of these services. Supporting mental health consumers can be burdensome which, in conjunction with the anguish that may result from observing their relative develop a mental illness, can lead to carers experiencing significant levels of distress. Aims: This study aimed to quantify the extent to which specific aspects of caregiving contribute to mental health burden in Australia. Methods: Participants were included if they were Australian mental health caregivers. An online questionnaire was distributed via email. Multivariate logistic regression was used to identify predictors of burden in mental health caregivers. Results: Completed questionnaires were collected from 231 respondents. The logistic regression analysis yielded five factors that contributed significantly to mental health caregiver burden. Of these factors, a strained atmosphere and regularly carrying out tasks for consumers were the two strongest predictors of burden. Conclusion: Community health professionals could focus on interpersonal relationships between family members, access to disability and financial support services, and carers' views about the quality of healthcare provided to consumers. Addressing these issues may decrease carer burden and improve the quality of life for all family members.